Flooded pasts: UNESCO, Nubia, and the recolonization of archaeology - Carruthers, William (Cornell University Press, 2022)
"Examines a world famous yet critically under-examined event-UNESCO's 1960-80 International Campaign to Save the Monuments of Nubia-to show how the project, its genealogy, and its aftermath not only helped to propel archaeology into a changing world but also helped to 'recolonize' it"--